EFEKTIVITAS PENERAPAN E-TAX DALAM MONITORING PAJAK RESTORAN DI KOTA SEMARANG - Aldo Nizar Farozin; Tri Yuniningsih; Agustin Rina Herawati (Journal of Public Policy and Management Review, 2023)
E-Tax is an online business transaction recording tool that is used in the tax administration system presented by the Regional Revenue Agency of Semarang City. With this e-tax, it is hoped that the government's goal of improving the taxpayer payment monitoring system for this business can be achieved, and the installation of e-tax in every restaurant to avoid fictitious reports because the tool can find out real daily income. Recording data from the receipt is directly entered on the Semarang City Online Tax Monitoring Website. This study aims to analyze the effectiveness of implementing e-tax in monitoring restaurant taxes in the city of Semarang and analyze the supporting and inhibiting factors. This study uses qualitative research methods where data is obtained through interviews, observation, and documentation. The results of this study include several indicators of the effectiveness of implementing e-tax. The indicators include Target Accuracy, Program Socialization, Goal Achievement, and Monitoring. The researcher also found obstacles to implementing e-tax in monitoring restaurant taxes in the form of network disruptions so that they could not open applications that were connected to installed e-tax and such as broken e-tax devices so that they could not function. Another obstacle was the lack of participation of restaurant taxpayers who did not want to install e-tax or fraud committed by the taxpayer himself. The conclusions from the research are that monitoring is not running effectively due to the lack of human resources in the field to directly supervise if fraud or e-tax repairs occur and the lack of maximum public awareness of tax compliance. Suggestions in the research are the formation of a task force team to carry out supervision in the field related to fraud in the use of e-tax while also carrying out data collection, dissemination of e-tax and routine monitoring of new taxpayers.